Cert Prep: Microsoft Windows Client (MD-100). - Ballew, Joli (linkedin.com, 2023)
Go over the latest exam blueprint for the Managing Modern Desktops exam, one of two exams for learners looking to earn their Modern Desktop Administrator Associate Certification.